2017
DOI: 10.1159/000484175
|View full text |Cite
|
Sign up to set email alerts
|

NSCLC Patients Harbouring Rare or Complex EGFR Mutations Are More Often Smokers and Might Not Benefit from First-Line Tyrosine Kinase Inhibitor Therapy

Abstract: Background: Generally, tyrosine kinase inhibitor (TKI) therapy is recommended in first-line treatment of patients with advanced non-small cell lung cancer (NSCLC) harbouring a classic epidermal growth factor receptor (EGFR) mutation. However, the response of patients with rare or complex EGFR mutations to TKI treatment is not predictable, nor is the prognosis for such patients. Objectives: In cases of rare or complex EGFR mutations, the right approach to therapy remains challenging. That is why we sought to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
5
12
0
Order By: Relevance
“…Within our cohort, there was a trend toward more frequent uncommon EGFR mutations among ES patients, although statistically not significant, which is consistent with other Asian studies 4,31. On the other hand, a significant association of EGFR uncommon mutations with smoking has been described amongst European lung cancer patients 32…”
Section: Discussionsupporting
confidence: 91%
“…Within our cohort, there was a trend toward more frequent uncommon EGFR mutations among ES patients, although statistically not significant, which is consistent with other Asian studies 4,31. On the other hand, a significant association of EGFR uncommon mutations with smoking has been described amongst European lung cancer patients 32…”
Section: Discussionsupporting
confidence: 91%
“…In this study, 3.3% of cases with rare-type EGFR mutations were not detected using PCR. Rare EGFR mutations had been reported to be observed in male smokers with inferior EGFR TKI response [13,14]. However, recent studies have reported that rare EGFR mutations can be more effectively targetable with appropriate TKIs [15].…”
Section: Discussionmentioning
confidence: 99%
“…In another report, a patient with co-existence of I706T and G719A had a good response and a PFS of at least 22 months, but a patient with co-existence of E709K and G719A had a very poor response to EGFR TKI [ 27 ]. Kauffmann-Guerrero et al reported a patient with co-existence of G857E and R836R in exon 21, who had a very poor response to EGFR TKI [ 12 ]. In our current study, interestingly, all of five patients with stage IV adenocarcinoma harboring a sensitizing mutation and a resistant uncommon mutation involved two point mutations in a single exon (exon 18 G719X with another exon 18 point mutation).…”
Section: Discussionmentioning
confidence: 99%
“…Of all EGFR mutations in lung cancer, approximately 90% are common mutations, including in-frame deletions in exon 19 and an L858R point mutation in exon 21 [ 5 , 6 , 7 ]. However, many uncommon mutations, also called rare or non-classical mutations, were detected but the response to EGFR TKIs was inconsistent due to a limited number of cases enrolled in the trials [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. For example, Chiu et al claimed that both gefitinib and erlotinib are active in lung adenocarcinoma patients with G719X/L861Q/S768I mutations but they had short PFS (a median of 7.7 months) than in those with common EGFR mutations (a median of 11.4 months) ( p < 0.01) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%